2022
DOI: 10.1136/lupus-2021-000631
|View full text |Cite
|
Sign up to set email alerts
|

Clinical measurement of lupus nephritis activity is inferior to biomarker-based activity assessment using the renal activity index for lupus nephritis in childhood-onset systemic lupus erythematosus

Abstract: ObjectivesThe renal activity index for lupus (RAIL) measures lupus nephritis (LN) activity considering urine levels of 6 biomarkers (neutrophil gelatinase-associated lipocalin, monocyte chemoattractant protein-1, kidney injury molecule-1, adiponectin, haemopexin, ceruloplasmin). We aimed to compare the accuracy of the RAIL and the renal domain-score of the SLE disease activity index (rSLEDAI) in detecting LN activity.MethodsRandom urine samples of patients with childhood-onset SLE with and without LN were assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…In this context, RAIL scores will provide additional support for the biologic relevance of the observed response of LN to a given treatment intervention. Importantly, corrected for treatment response, we have shown consistently in the past that changes in RAIL scores are not influenced by the type of concurrent therapies, including the use of proteinuriasparing agents [12][13][14]40].…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In this context, RAIL scores will provide additional support for the biologic relevance of the observed response of LN to a given treatment intervention. Importantly, corrected for treatment response, we have shown consistently in the past that changes in RAIL scores are not influenced by the type of concurrent therapies, including the use of proteinuriasparing agents [12][13][14]40].…”
Section: Discussionmentioning
confidence: 73%
“…Likewise, the standardized adult RAIL score of − 0.97 or higher correctly identifies older patients with active LN with 86% accuracy [13]. We have also shown that the accuracy of pRAIL scores to identify active LN does not require urine creatinine adjustment, and that scores ≥ 2 are consistent with a NIH Activity Index (NIH-AI) value of 10 or higher, while pRAIL scores of 0 or less are consistent with NIH-AI values of 2 or less [14]. RAIL scores decrease (or improve) with immunosuppressive therapy in those with treatment response [11,12].…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations